PENERAPAN SISTEM NILAI CACAT PADA KOMODITAS KOPI ROBUSTA (Studi Kasus di Wonokerso, Pringsurat, Temanggung) - Alfina Handayani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
Coffee is one of the leading products in the plantation subsector in Indonesia. This study aims to test the quality of coffee by defec system established by the SNI (Indonesia National Standart). The study took place from July to September 2012. Coffee samples obtained from 20 coffee farmers in the Wonokerso village that drawn at random sampling and each of them took 300 grams of coffee beans. Coffee quality testing conducted at the Research and Development Center of Central Java Province and Food Technology Laboratory UNIKA Soegijapranata Semarang. The results showed that coffee quality is compliant with the general quality, there are free from insects and mold odor, the average water content of the samples had 10.73% or below 12%. maximum water content is 12,57% and the lowest 8.73%. The levels of impurities below 0.5%.